Desirable Elements for a Particle System Interface. (5th January 2014) - Schroeder, Daniel; Hamilton, Howard J.
Abstract : Particle systems have many applications, with the most popular being to produce special effects in video games and films. To permit particle systems to be created quickly and easily, Particle System Interfaces (PSIs) have been developed. A PSI is a piece of software designed to perform common tasks related to particle systems for clients, while providing them with a set of parameters whose values can be adjusted to create different particle systems. Most PSIs are inflexible, and when clients require functionality that is not supported by the PSI they are using, they are forced to either find another PSI that meets their requirements or, more commonly, create their own particle system or PSI from scratch. This paper presents three original contributions. First, it identifies 18 features that a PSI should provide in order to be capable of creating diverse effects. If these features are implemented in a PSI, clients will be more likely to be able to accomplish all desired effects related to particle systems with one PSI. Secondly, it introduces a novel use of events to determine, at run time, which particle system code to execute in each frame. Thirdly, it describes a software architecture called the Dynamic Particle System Framework (DPSF). Simulation results show that DPSF possesses all 18 desirable features.